2014
DOI: 10.1002/art.38804
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cellular and Humoral Immunity to Varicella‐Zoster Virus in Patients With Autoimmune Diseases

Abstract: Objective. Patients with autoimmune diseases such as systemic lupus erythematosus (SLE) and granulomatosis with polyangiitis (Wegener's) (GPA) have a 3-20-fold increased risk of herpes zoster compared to the general population. The aim of this study was to evaluate if susceptibility is due to decreased levels of cellular and/or humoral immunity to the varicellazoster virus (VZV).Methods. A cross-sectional study of VZV-specific immunity was performed in 38 SLE patients, 33 GPA patients, and 51 healthy controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 30 publications
9
50
0
3
Order By: Relevance
“…in the case of varicella control, is highlighted by the inverse correlation of viral load and frequencies of cytokine-producing Th-cells (37); similar findings were reported for SLE patients being at high risk for viral reactivation correlating with diminished anti-viral T cell responses (38). Our very recent data on BKVspecific T cell responses and BK viremia in renal transplant population further support the crucial role of cellular immunity (39).…”
Section: Discussionsupporting
confidence: 81%
“…in the case of varicella control, is highlighted by the inverse correlation of viral load and frequencies of cytokine-producing Th-cells (37); similar findings were reported for SLE patients being at high risk for viral reactivation correlating with diminished anti-viral T cell responses (38). Our very recent data on BKVspecific T cell responses and BK viremia in renal transplant population further support the crucial role of cellular immunity (39).…”
Section: Discussionsupporting
confidence: 81%
“…The prevalence of herpes zoster in SLE has increased, and risk of herpes zoster is associated with lymphopenia, increased use of corticosteroids, and most types of immunosuppressive therapy [45-47]. A poor cellular immunity, including decreased IFN-γ releasing cells and CD4+ T cells in response to VZV, is correlated with VZV infection and SLE [48]. CMV infection can be presented as CMV retinitis, CMV colitis, or CMV pneumonitis in patients with SLE, and may result in a systemic inflammation mimicking SLE [49].…”
Section: Infection As a Vulnerable Point In Slementioning
confidence: 99%
“…Moreover, Chakravarty et al demonstrated that SLE patients had an increased incidence of herpes zoster in comparison to patients with non-inflammatory musculoskeletal conditions, and that the use of prednisone and MMF was an additional risk factor for the infection among SLE patients [13]. Rondaan et al reported that cellular immunity to VZV was decreased in patients with SLE, whereas it was comparable to that in healthy controls in patients who had granulomatosis with polyangiitis [21]. …”
Section: Discussionmentioning
confidence: 99%